Formulation and antibacterial activity of black mulberry fruit (Morus nigra L.) extract cream against cutibacterium acnes and staphylococcus epidermidis - Yola Desnera Putri; Lisna Munawaroh; Ledianasari Ledianasari; Adit Andriyannto (Institute of Computer Science (IOCS), 2026)
Acne vulgaris is an inflammatory disorder of the pilosebaceous unit characterized by sebum overproduction, abnormal keratinization, microbial proliferation, and inflammation, with Propionibacterium acnes and Staphylococcus epidermidis as key contributing bacteria. To reduce the side effects associated with conventional acne therapies, natural ingredients have been explored as alternative approaches. Black mulberry (Morus nigra) fruit is one such natural source known to contain bioactive compounds, including flavonoids, tannins, and terpenoids, which possess antibacterial properties. This study aimed to develop and evaluate a topical cream formulation containing ethanolic extract of black mulberry fruit and to assess its antibacterial activity and physicochemical stability. The extract was obtained through 96% ethanol maceration and formulated into creams at concentrations of 1.25%, 2.5%, and 5%. Antibacterial activity was evaluated using the agar well diffusion method, while cream quality was assessed through organoleptic properties, homogeneity, pH, viscosity, spreadability, and centrifugation stability. The results showed that the extract exhibited strong antibacterial activity against both tested bacteria. All concentrations demonstrated inhibition zones categorized as strong, with a concentration-dependent increase in activity. At 1.25% inhibition zones against P. acnes were 11.7 ± 0.25 m, while against S. epidermidis were 11.9 ± 0.20 mm at day 28. All formulations showed acceptable physicochemical characteristics and remained stable during 28 days of storage. The novelty of this study lies in the development of a stable topical cream formulation of M. nigra extract with confirmed antibacterial activity, providing a potential plant-based alternative for anti-acne therapy.